Telomere Shortening, Regenerative Capacity, and Cardiovascular Outcomes - Hammadah, Muhammad (Circ Res, 2016)
RATIONALE: Leucocyte telomere length (LTL) is a biological marker of aging, and shorter LTL is associated with adverse cardiovascular outcomes. Reduced regenerative capacity has been proposed as a mechanism. Bone marrow-derived circulating progenitor cells (PCs) are involved in tissue repair and regeneration. OBJECTIVE: To examine the relationship between LTL and PCs, and their impact on adverse cardiovascular outcomes. METHODS AND RESULTS: We measured LTL by quantitative PCR in 566 outpatients (age 63±9 years, 76% male) with coronary artery disease (CAD). Circulating PCs were enumerated by flow cytometry. After adjustment for age, gender, race, BMI, smoking and previous myocardial infarction, a shorter LTL was associated with a lower CD34(+) cell count: for each 10% shorter LTL, CD34(+) levels were 5.2% lower (p<0.001). After adjustment for the aforementioned factors, both short LTL (<Q1) and low CD34+ levels (<Q1) predicted adverse cardiovascular outcomes (death, myocardial infarction, coronary revascularization or cerebrovascular events) independently of each other, with a hazards ratio (HR) of 1.8, 95% confidence interval (CI), 1.1–2.0, and a HR of 2.1, 95% CI, 1.3–3.0, respectively, comparing Q1 to Q2–4. Patients who had both short LTL (<Q1) and low CD34+ cell count (<Q1), had the greatest risk of adverse outcomes (HR=3.5, 95% CI, 1.7–7.1). CONCLUSION: Although shorter LTL is associated with decreased regenerative capacity, both LTL and circulating PC levels are independent and additive predictors of adverse cardiovascular outcomes in CAD patients. Our results suggest that both biological aging and reduced regenerative capacity contribute to cardiovascular events, independent of conventional risk factors.